Applications of Unmanned Aerial Systems in Agricultural Operation Management: Part II: Platforms and Payloads - Aditya Singh; James Fletcher (EDIS)
Unmanned aerial systems (UASs, UAVs, or drones) have emerged as an important tool for farmers, Extension agents, and landowners to map, monitor, and manage their properties. This 5-page publication provides an overview of the primary components of typical UASs to help growers, landowners, and/or Extension agents who want to configure and/or purchase a UAS or sensor system for agricultural operations. This document is one of a three-part series focusing on the applications, configuration, and best practices for using UASs in agricultural operations management. Written by Aditya Singh and James Fletcher, and published by the UF/IFAS Department of Agricultural and Biological Engineering, February 2021.